2006
DOI: 10.1002/eat.2260040421
|View full text |Cite
|
Sign up to set email alerts
|

Some reflections on the nature of the eating disorders: On the need for humility

Abstract: For a long time, perhaps until as recently as about 1970, a person hospitalized for anorexia nervosa (AN) or bulimia was considered a sufficient rarity as to virtually guarantee his or her presentation at psychiatric or medical grand rounds. The esoteric nature of these diagnoses has changed dramatically in recent years, presumably as a consequence of an increase in both diagnostic sensitivity and actual incidence. Concomitantly, there has been a virtual explosion in serious clinical writings and research abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Psychological, biological and social factors are implicated in the development of eating disorders (Katz 1985;Garner et al 1987). Athletes appear to be more vulnerable to eating disorders than the general population, because of additional stresses associated with the athletic environment (Hamilton et al 1985;Szmuckler et al 1985).…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological, biological and social factors are implicated in the development of eating disorders (Katz 1985;Garner et al 1987). Athletes appear to be more vulnerable to eating disorders than the general population, because of additional stresses associated with the athletic environment (Hamilton et al 1985;Szmuckler et al 1985).…”
Section: Risk Factorsmentioning
confidence: 99%
“…emphasis on leanness or individual competition) may interact with the personality traits of the athlete to start or perpetuate an eating disorder (Wilson & Eldredge 1992). Finally, athletes have reported that they developed eating disorders as a result of an injury or illness that left them temporarily unable to continue their normal level of exercise (Katz 1985;Sundgot-Borgen 1994a). An injury can curtail the athlete's exercise and training habits.…”
Section: Risk Factorsmentioning
confidence: 99%